Preparation and characterization of starch-poly-epsilon-caprolactone microparticles incorporating bioactive agents for drug delivery and tissue engineering applications - Balmayor, Elizabeth Rosado (2009)
One limitation associated with the delivery of bioactive agents concerns the short half-life of these molecules when administered intravenously, which results in their loss from the desired site. Incorporation of bioactive agents into depot vehicles provides a means to increase their persistence at the disease site. Major issues are involved in the development of a proper carrier system able to deliver the correct drug, at the desired dose, place and time. In this work, starch-poly-e-caprolactone (SPCL) microparticles were developed for use in drug delivery and tissue engineering (TE) applications. SPCL microparticles were prepared by using an emulsion solvent extraction/evaporation technique, which was demonstrated to be a successful procedure to obtain particles with a spherical shape (particle size between 5 and 900 lm) and exhibiting different surface morphologies. Their chemical structure was confirmed by Fourier transform infrared spectroscopy. To evaluate the potential of the developed microparticles as a drug delivery system, dexamethasone (DEX) was used as model drug. DEX, a well-known component of osteogenic differentiation media, was entrapped into SPCL microparticles at different percentages up to 93%. The encapsulation efficiency was found to be dependent on the polymer concentration and drug-to-polymer ratio. The initial DEX release seems to be governed mainly by diffusion, and it is expected that the remaining DEX will be released when the polymeric matrix starts to degrade. In this work it was demonstrated that SPCL microparticles containing DEX can be successfully prepared and that these microparticular systems seem to be quite promising for controlled release applications, namely as carriers of important differentiation agents in TE.